TILLICH’S VIEW ON THE DEVELOPMENT OF CAPITALISM - Rachmat, Agus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
Driven by his method of correlation, Paul Tillich critically analyzes the social condition of modern society which is characterized by the growing hegemony of capitalism. Capitalism is viewed not simply as a certain economic arrangement of society but as the embodiment of the religion of reason, namely, the historical project of humanity to realize its utopian goals and longings by the power of science and technology alone. However, by forgetting the awareness of the inherent finitude of reason cultivated by a genuine religious consciousness, mankind is threatened to lose sight of the demonic dimension built-in structurally in the capitalist mode of wealth creation.